Atlas of Diagnostically Challenging Melanocytic Neoplasms - Longo, Caterina (Springer International Publishing, 2018)
This atlas provides a clear, concise overview of the most challenging circumstances faced by clinicians and pathologists when dealing with melanocytic neoplasms. The book is structured as a case series; for each case, the clinical and dermoscopic appearances are presented, accompanied by a brief but comprehensive description and compelling histopathologic images. When available, in vivo confocal microscopy images are also included to highlight additional diagnostic clues. Identification of key messages and selected references will further guide the reader in the diagnosis and management of the neoplasm under consideration. It is well known that melanocytic lesions can be difficult to interpret. Some lesions show an ambiguous combination of morphologic criteria, and in these cases interpretation entails a high degree of subjectivity that results in low interobserver agreement even among expert pathologists. This atlas demonstrates how the addition of clinical information, including that provided by dermoscopy, can assist in reaching a more confident diagnosis.